Kepentingan stesen kerja ergonomik terhadap kesihatan pekerjaan: Kajian ke atas organisasi multinasional di Malaysia - Makhbul, Zafir Mohamed; Idrus, Durrishah; Abdul Rani, Mat Rebi (Universiti Utara Malaysia, 2008)
Purpose - the occurrence of work stress is quite rampant in manufacturing organisations which involve-collar workers. The literature revealed that a poor ergonomic workstation environment is among the major contributors to occupational health problems.Thus, this study aimed to examine the relationship between ergonomic workstation factors and occupational health. Design/Methodology/Approach - A sample of 500 manufacturing operators were derived from 11 manufacturing electronics organisations which were registered with Malaysian International Chamber of Commerce and Industry (MICCI) by using proportionate stratified random sampling. Questionnaires were used for the data collections process. Finding - The major finding showed that an ergonomically designed workstation is an important strategy in minimising occupational health problems. These findings were supported by the Pearson correlation analysis which showed that all of these ergonomic workstation factors have high significant correlation with occupational health. Originality/Value - The findings of this research are important to organizations which are in need of healthy and competent human resource in-line with the aspiration of a dynamic human capital development. Paper Type - Research Paper.